A simulation sickness study on a driving simulator equipped with a vibration platform. (January 2020) - Lucas, Guillaume; Kemeny, Andras; Paillot, Damien; Colombet, Florent
Highlights: Some specific seat vibration configurations can have a positive impact on simulator sickness. Vibration system on driving simulator can be more useful than just improving the immersion. Consistent vibrations may have a better impact than other vibrations. Abstract: Simulator sickness is a well-known side effect of driving simulation which may reduce the passenger well-being and performance due to its various symptoms, from pallor to vomiting. Numerous reducing countermeasures have been previously tested; however, they often have undesirable side effects. The present study investigated the possible effect of seat vibrations on simulator sickness. Three configurations were tested: no vibrations, realistic ones and some that might affect the proprioception. Twenty-nine participants were exposed to the three configurations on a four-minute long automated driving in a simulator equipped with a vibration platform. Simulator sickness was estimated thanks to the Simulator Sickness Questionnaire (SSQ) and to a postural instability measure. Results showed that vibrations help to reduce the sickness. Our findings demonstrate that some specific vibration configurations may have a positive impact on the sickness, thus confirming the usefulness of devices reproducing the road vibrations in addition to creating more immersion for the driver.